Mechanochemical Synthesis of Lead-Free Perovskite-Like MA3Bi2I9 for Photo-Catalytic Hydrogen Production - Ahmad, Khursheed; Raza, Waseem; Kumar, Praveen; Khan, Mohd Quasim; Alsalme, Ali; Kim, Haekyoung (Chemistry - A European Journal, 2023)
In this study, a highly air stable and eco-friendly methyl ammonium bismuth iodide (MA3Bi2I9) perovskite-like material has been prepared. After physiochemical characterizations, the synthesized MA3Bi2I9 was utilized as photo-catalyst towards hydrogen production. It is important to design and synthesize lead (Pb)-free perovskite-like material (MA3Bi2I9) for photo-catalytic hydrogen-production applications. The synthesized MA3Bi2I9 exhibits excellent photo-catalytic hydrogen generation with a production rate of 11.43 μmolg−1 h−1. In the presence of a platinum co-catalyst, the hydrogen production rate further increases to 172.44 μmolg−1 h−1. The MA3Bi2I9 photo-catalyst also demonstrates excellent cyclic stability.
CRIS-Team Scopus Importer:2023-03-31
Keywords: hydrogen production; MA; Pb-free perovskite-like materials; photo-catalysis